Loading…

Flash Player 9 (or above) is needed to view presentations.
We have detected that you do not have it on your computer. To install it, go here.

Like this presentation? Why not share!

Funciones en forma de resta

on

  • 926 views

Tarea de Algebra con Diana C. Mex

Tarea de Algebra con Diana C. Mex

Statistics

Views

Total Views
926
Views on SlideShare
926
Embed Views
0

Actions

Likes
0
Downloads
3
Comments
0

0 Embeds 0

No embeds

Accessibility

Categories

Upload Details

Uploaded via as Microsoft PowerPoint

Usage Rights

© All Rights Reserved

Report content

Flagged as inappropriate Flag as inappropriate
Flag as inappropriate

Select your reason for flagging this presentation as inappropriate.

Cancel
  • Full Name Full Name Comment goes here.
    Are you sure you want to
    Your message goes here
    Processing…
Post Comment
Edit your comment

    Funciones en forma de resta Funciones en forma de resta Presentation Transcript

    • FUNCIONES EN FORMA DE RESTA
    • Integrantes :
      Enma de la cruz Chi
      Oscar Encalada Sarricolea
      Ytati Pech Marín
      Cinthia Novelo Sansores
      Shana Martínez Gutiérrez
    • Funciones lineales negativas:
      F(x)= 2x-3
      Df= {X/XE IR}
      Rf= {Y/Y E IR}
    • EJEMPLOS: funciones cuadráticas
      F(x)= ax2F(X)=2X2-4
      DF= {X/XE IR}
      RF= {Y/Y mayores iguales que -4}
    • F(X)=x2-2x-3
      DF= {X/XE IR}
      RF= {Y/Y menoresiguales que 3}
    • FUNCION CUADRATICA DE LA FORMA f(x)= ax2+bx+c
    • Funciones cubicas
      Del tipo ax3
      Del tipo –ax3+bx2+cx+d
    • F(x):x3+4x2–x-4
      F(0)=(0)3+4(0)-0-4 (0,-4) -5 , 63
      =-4 2 8
      Raíces:
      F(x)=x(x2-1)+4(x2 -1)
      f(x)= (x+4)(x-1)(x+1)
      X+4=0 x-1=0 x-1
      X=-4 x=1 x=-1
      Puntos de retorno:
      x1 +x2 = -4+1(-1) = -5
      2 2 2
      b) x1+x2= -1+1= 0 = 0
      2 2 2
      F(-5/2)= (-5/2)3 +4(-5/2)2–(-5/2)-4
      =63 -5,63
      8 2 8
    • Funciones por partes
      F(x)= x2-1 si -2 ≤ x ≤ 2
      x2-2 si 2≤ x ≤5
    • Función radical
      F(x) - √ c-x2
      D[- √c, √c]
      R[0,- √c]
    • y=- √x+c
      Y=- √X
      D[0,+ ∞]
      R [0,- ∞]
      X+C ≥0
      X ≥e